Fotografía y práctica performativa : Reflexiones sobre Apnea y Moisés - Santiago, Estefanía (2018)
Focusing on the work of two Argentinian photographers —Apnea (2014-2015), by Cecilia Lutufyan, and Moisés (2014-2015), by Mariela Sancari— this work reflects on the place that the performative practice occupies in the language of photography. In both conceptual quests, the death, which makes an absence visible, is questioned and, through the participation of other factors foreign to the project a performed situation is constructed. This situation is the central theme of the representation process that questions the photography as document of what is real.